Application of The Temperature Shock Method (Heat Shock) on Pearl Oyster (Pinctada maxima) Hatcheries - Lusiana BR Ritonga (Journal of Aquaculture Development and Environment, 2022)
The low production and quality of pearls produced from the cultivation process, one of which iscaused by the less than optimal quality of pearl oysters. Spawning is a determining factor in hatcheryactivities. Therefore, in an effort to increase production, it requires strategies and improvements inthe pearl oyster spawning process. This study aims to apply the temperature shock method as an effortto increase productivity and success rate of pearl oyster hatchery. The results of observations ongonad maturity in pearl oyster broodstock obtained data from a total of 200 broods consisting of 135male broods and 75 female brooders aged 3.5 years, the percentage of perfectly gonadally maturebroodstock was 11.85% and 12%, respectively a total of 25 individuals. The results of spawning pearloyster broodstock through the temperature shock method of a total of 18 broods observed were 12brooders or 66.7% which spawned perfectly. The results of the observation of the spawning process ofpearl oyster broodstock showed that from 8 female broodstock ± 90,000,000 eggs were obtained witha hatching rate of 70% with a spat harvest of ± 1,575,000 individuals or 2.5% of the total hatchedlarvae final yield.